Rancang Bangun Sistem Informasi Ekstrakurikuler Esport Berbasis Web pada SMK PGRI 1 Tangerang - Aditya Gigih Prayogo; Afiani Agus Abdillah; Hafid Dwi Januar; Ridho Firdaus (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Extracurricular activities are an important part of supporting the development of students' interests, talents, and character. However, the management of extracurricular activities at SMK PGRI 1 Tangerang is still done manually, leading to various problems such as delays in information delivery, data recording errors, and difficulties in reporting. Therefore, an information system is needed to facilitate more effective and efficient management of extracurricular activities. The system development method used is the Waterfall method, which includes needs analysis, system design, implementation, testing, and maintenance. The system developed includes key features such as extracurricular data management, online attendance, activity information delivery, and report generation. With this system implementation, SMK PGRI 1 Tangerang can manage data and provide information quickly, effectively, and accurately. This improves the effectiveness of extracurricular activity management and the quality of information services for students.